Increased exhaled nitric oxide and its oxidation metabolism in eosinophilic chronic rhinosinusitis - Takeno, Sachio; Taruya, Takayuki; Ueda, Tsutomu; Noda, Noriaki; Hirakawa, Katsuhiro (Auris, nasus, larynx, 2013)
Monitoring of fractional concentrations of exhaled nitric oxide (FeNO) has become a reliable marker of inflammation in human nose and paranasal sinuses. However, it is still unknown to what extent nasal NO levels contribute to the pathology of chronic rhinosinusitis (CRS). In the present study, we aimed to examine FeNO levels and the underlying mechanism of NO production and metabolism in patients with eosinophilic chronic rhinosinusitis (ECRS) and non-ECRS. Thirty-three untreated ECRS patients, 16 non-ECRS patients, and 38 normal subjects were enrolled in this cross-sectional study of FeNO levels. Oral and nasal FeNO levels were measured before treatment using an electrochemical NO analyzer (NObreath®) with a nose adaptor. The mRNA expression of three nitric oxide synthase (NOS) isoforms, interleukin-5 (IL-5), and transforming growth factor-beta (TGF-β) in the ethmoid sinus mucosa and nasal polyps were analyzed by real-time PCR. Immunohistological localization of inducible NOS (iNOS) and nitrotyrosine (NT), a marker for oxidized NO metabolites, was also examined. ECRS patients showed significantly higher oral FeNO levels compared to non-ECRS patients and normal subjects (mean values, 47.6, 13.5, and 15.3ppb, respectively). Nasal FeNO levels of the non-ECRS patients (30.5ppb) were significantly lower than those of the ECRS patients (53.9ppb) and normal subjects (45.5ppb). Positive correlations existed between the blood eosinophil percentage and FeNO levels in ECRS patients. Histologically, ECRS patients showed higher eosinophil accumulation in the ethmoid mucosa than non-ECRS patients (103.1 vs. 16.3cells/HPF). Real-time PCR analysis showed significant upregulation of iNOS and IL-5 mRNA expression in the ethmoid mucosa of the ECRS patients compared to those of non-ECRS patients. Positive iNOS immunoreactivity was observed in ciliated epithelial cells, submucosal glands and associated inflammatory cells in both groups. NT immunoreactivity was detected in the epithelium and around inflammatory cells. Intense NT staining was co-localized with eosinophil accumulation and ECRS patients showed significantly higher rates of NT-positive cells than non-ECRS patients. A combination of oral and nasal FeNO measurement is a valid marker for the classification and definition of different CRS subtypes in Japan. Higher levels of oral and nasal FeNO in ECRS patients may reflect the persistence of eosinophilic inflammation in sinus mucosa with concomitant iNOS upregulation and accompanying deposition of oxidized NO metabolites.